A Civic Center or the Requiem of the Costa Rican Urban - Muñoz Muñoz, Marcela (2017)
This article offers a posthumous honor for public architecture of the Costa Rican capital, San José, as a national model of a city. The study of the discussion contained in certain legislative acts around the convenience to give the country a National Civic Center, [do not] favors the understanding of an emerging Urban Planning before 1970’s, the “legal” decade for the Urban Law. By using the analogy of the requiem, the History of Urban Law demands the futility of legal solutions to save valuable buildings that were born in the formation of the National State, during the 19th and 20th centuries. The Costa Rica ́s quest for modernity claims for new ways where Law can understand Urban Heritage.